Intensive feeding of milkfish fry (Chanos Chanos Forsskal) in net enclosures using complete and incomplete diets at various protein levels - Seraspe, Ebonia
Twenty-six net enclosures (approximately 1 m³ ) suspended in a brackishwater pond were used to grow milkfish fry (0.01 g average weight) to fingerling (0.75 g average weight) for 64 days to determine whether supplemental feeding will increase growth and survival of fry; whether it is best to give vitamin-enriched feed and what level of protein is considered optima for milkfish fry. suitability of net enclosure for rearing milkfish fry was also assesses. four levels of crude protein (20%, 30%, 40%, and 50%) in complete and incomplete formulations were evaluated and assigned randomly among the experimental units. Feeds were given in fine crumbles, at 8% to 6% of total body weight on a dry weight basis for six days a week. survival was higher in complete diet regime than in incomplete diet regime but there was no significant difference with regards to growth. forty percent (40%) was found to be the optimum level of protein for. maximm growth of the milkfish fry. Limitations for rearing fry in cages were met such as fouling of the net, low water interchange in the net, increased labor costs for handling, feeding and cage maintenance.